2002
DOI: 10.2478/v10050-008-0077-z
|View full text |Cite
|
Sign up to set email alerts
|

Stop-over of migrant Blackcaps (Sylvia atricapilla) on autumn passage through the Polish Baltic coast

Abstract: In this analysis, data on Blackcaps caught on autumn migration at the Operation Baltic stations: Bukowo-Kopañ (54°28N, 16°25E) in 1984-1999 and Mierzeja Wilana (54°21N, 18°19E) in 1982-1999 14 August 1 November) were used.Total percentage of stopping-over (retrapped) Blackcaps was 11.6% at Mierzeja Wilana and 7.9% at Bukowo-Kopañ station. On average birds stayed longer at Mierzeja Wilana (median 5 days) than at Bukowo-Kopañ (median 4 days). Most probably, the Blackcap stop-over length and frequency depended o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The Blackcap migration in central Europe begins in August, is most intensive in September, and ends in early-or mid-October, as shown on the Polish Baltic coast (Kopiec 1997, Kopiec-Mokwa 1999, Polish inland (Tomia³ojae & Stawarczyk 2003) and at the German ringing stations Reit and Mettnau (median dates of the passage were 31 August at Reit and 20 September at Mettnau; Berthold et al 1991), while the median date of autumn migration at Helgoland was 1 October (Hüppop & Hüppop 2004). In Norway, autumn migration also begins in August (Bakken et al 2006), while median dates are similar to those observed in central Europe (Jomfruland: 20 September, Lista: 30 September; Hüppop & Hüppop 2004).…”
Section: Discussionmentioning
confidence: 96%
“…The Blackcap migration in central Europe begins in August, is most intensive in September, and ends in early-or mid-October, as shown on the Polish Baltic coast (Kopiec 1997, Kopiec-Mokwa 1999, Polish inland (Tomia³ojae & Stawarczyk 2003) and at the German ringing stations Reit and Mettnau (median dates of the passage were 31 August at Reit and 20 September at Mettnau; Berthold et al 1991), while the median date of autumn migration at Helgoland was 1 October (Hüppop & Hüppop 2004). In Norway, autumn migration also begins in August (Bakken et al 2006), while median dates are similar to those observed in central Europe (Jomfruland: 20 September, Lista: 30 September; Hüppop & Hüppop 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Strong wind and low temperature influence migrating birds to similar extent and after retreat birds should continue their migration (Rabøl andPettersen 1973, Mehlum 1983). Internal factors cause birds to restore energy reserves (Pettersson and Hasselquist 1985, Ganness 2002, Kêdzior 2002. The relation between these groups of factors has an effect on duration of flight and stopover (Jenni and Schaub 2004).…”
Section: Factors Influencing Stopover In Migrantsmentioning
confidence: 99%
“…Geographical location, habitat conditions at recapture sites and migratory strategy of species probably play an important role in frequency of birds stopover, time that birds spend at certain area and fat-weight relationship (Karlsson et al 1988, Ehnbom et al 1993, Kêdzior 2002. The aim of our study is to compare stopover duration, body condition (fat reserves, body weight) and age structure of Robins caught at different stopover sites.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has already been used in some papers (e.g. Busse 1976, Kêdzior 2002, Zakala et al 2004.…”
Section: Introductionmentioning
confidence: 99%